Potential Sites for Underground Energy and CO2 Storage in Greece: A Geological and Petrological Approach - Apostolos Arvanitis; Petros Koutsovitis; Nikolaos Koukouzas; Pavlos Tyrologou; Dimitris Karapanos; Christos Karkalis; Panagiotis Pomonis (Energies, 2020)
Underground geological energy and CO2 storage contribute to mitigation of anthropogenic greenhouse-gas emissions and climate change effects. The present study aims to present specific underground energy and CO2 storage sites in Greece. Thermal capacity calculations from twenty-two studied aquifers (4 × 10−4–25 × 10−3 MJ) indicate that those of Mesohellenic Trough (Northwest Greece), Western Thessaloniki basin and Botsara flysch (Northwestern Greece) exhibit the best performance. Heat capacity was investigated in fourteen aquifers (throughout North and South Greece) and three abandoned mines of Central Greece. Results indicate that aquifers present higher average total heat energy values (up to ~6.05 × 106 MWh(th)), whereas abandoned mines present significantly higher average area heat energy contents (up to ~5.44 × 106 MWh(th)). Estimations indicate that the Sappes, Serres and Komotini aquifers could cover the space heating energy consumption of East Macedonia-Thrace region. Underground gas storage was investigated in eight aquifers, four gas fields and three evaporite sites. Results indicate that Prinos and South Kavala gas fields (North Greece) could cover the electricity needs of households in East Macedonia and Thrace regions. Hydrogen storage capacity of Corfu and Kefalonia islands is 53,200 MWh(e). These values could cover the electricity needs of 6770 households in the Ionian islands. Petrographical and mineralogical studies of sandstone samples from the Mesohellenic Trough and Volos basalts (Central Greece) indicate that they could serve as potential sites for CO2 storage.